A Checklist on the Protozoan Parasites of Freshwater Fishes of Bangladesh (Bangladesh Journal of Zoology, 2020)
The current work has been proposed to accumulate baseline information regarding prevalence, diversity and distribution of the protozoan parasites found in the freshwater fishes of Bangladesh from its inception to 2019. This is an attempt to compile a baseline data on protozoan parasites of freshwater fishes in Bangladesh. A total of thirty four articles were reviewed whereas sixteen articles reported systematic, taxonomic and morphometric analysis of protozoan parasites, five articles described seasonal parasitic infestation in carp fishes including protozoan parasites, seven articles reported overall parasitic infestation along with protozoan infection, three articles described protozoan infection in consort with the histo-pathological analysis, one article revealed the occurrence of one protozoan parasite named Trypanosoma sp. and one study described monthly fluctuation of overall parasitic infection together with protozoan infestation. A number of thirty four freshwater fish species under nine orders in Bangladesh were retrieved on the mentioned articles and found 48 species of protozoan parasites under 19 genera. Noticeably, parasites under genus Trichodina was frequently found in the freshwater fish species. Most of the parasites were found from the gills (micro-habited) of the host fish. To sum up, from this compilation a primary database of protozoan parasites of freshwater fish species might be expected to establish that will be supportive for further extensive study.Bangladesh J. Zool. 48(1): 21-35, 2020